Analysis of transpression within contractional fault steps using finite-element method. (March 2017) - Nabavi, Seyed Tohid; Alavi, Seyed Ahmad; Mohammadi, Soheil; Ghassemi, Mohammad Reza; Frehner, Marcel
Abstract: Two-dimensional finite-element modelling of elastic Newtonian rheology is used to compute stress distribution and strain localization patterns in a transpression zone between two pre-existing right-stepping, left-lateral strike-slip fault segments. Three representative fault segment interactions are modelled: underlapping, neutral, and overlapping. The numerical results indicate that at the onset of deformation, displacement vectors are oblique to the regional compression direction (20–90°). The orientations of the local σ1 (the maximum compressive stress) and σ3 (the minimum compressive stress) directions strongly depend on the structural position within the transpression zone. For neutral and overlapping fault steps, there is a contractional linking damage zone between the fault segments. For overlapping faults, the σ1 trajectories within the transpression zone deflects significantly forming a sigmoidal pattern, which is created by two rotational flow patterns close to the fault tips. These flow patterns are related to friction effects and different shear deformation, from pure shear outside of the fault steps toward simple shear along the fault segments. Interaction between the two fault segments perturbs the stress field and reflects the heterogeneous nature of deformation. A lozenge- (for underlapping steps), rhomboidal- (for neutral steps), and sigmoidal-shaped (for overlapping steps) transpression zone developed between the two segments. The modelled mean stress pattern shows a similar pattern to that of the contractional steps, and decrease and increase in underlapping and overlapping fault steps, respectively. Comparison of the Kuh-e-Hori transpression zone, between the Esmail-abad and West Neh left-stepping right-lateral strike-slip fault segments in SE Iran, with the modelling results shows strong similarities with the neutral step configuration. Highlights: Overlap-to-separation ratio and convergence angle are main parameters affecting the development and pattern of transpression zones. Stress and strain trajectories rotation and variation in their magnitudes reflects the heterogeneous nature of deformation within transpression zone. Lozenge-, rhomboidal-, and sigmoidal-shaped transpression zones are characteristics of underlapping, neutral, and overlapping steps, respectively. Modelling of neutral step configuration strongly resemble the prototype Kuh-e-Hori transpression zone, SE Iran.